PEMBELAJARAN BERBASIS ETIKA ILMIAH UNTUK PENGUATAN KARAKTER SISWA SD - Yuni Ma’idah; Naning Tyas Ayu Hera Warsito; Muhamad Candra Ari Nata; Siti Mas’ula; Slamet Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines the implementation of scientific ethics–based learning as a strategy to strengthen the character of elementary school students. Scientific ethics refers to principles of honesty, objectivity, responsibility, and respect for human dignity that guide learning practices. The study employs a descriptive qualitative approach through interviews, classroom observations, and document analysis to describe how teachers apply ethical values in teaching. The findings show that teachers integrate scientific ethics through objective assessment, fair guidance, inquiry-based learning, and ethical use of technology. Teachers also adapt learning strategies for students with diverse abilities to ensure fairness and respect for student dignity. The study concludes that scientific ethics–based learning strengthens student character, enhances classroom interactions, and supports teachers in making humane and responsible pedagogical decisions. The results highlight the need for teacher training, integrity-oriented school policies, and strengthened ethical digital literacy in elementary education